PENGARUH PELAKSANAAN PENGAMPUNAN PAJAK (TAX AMNESTY) TERHADAP PENERIMAAN PAJAK PADA KPP PRATAMA JAKARTA CENGKARENG - seno sudarmono Hadi; Riovaldy Thewil Bindura (MONETER - JURNAL AKUNTANSI DAN KEUANGAN, 2018)
The role of taxes for the state is very important considering one of the sources of state cash receipts. The government's policy to increase state¬¬¬ revenues through the tax is the implementation of tax amnesty. The method used to examine the influence of tax amnesty on tax revenue at KPP Pratama Jakarta Cengkareng are observation, interview, and literature study with quantitative analysis that was analysis method using statistical analysis, with tax amnesty’s revenue as independent variable (X ) And tax revenue as the dependent variable (Y). The result showed that the correlation value was 0.791 with the probability of 0.011 which means the independent and the dependent variable has a strong and significant relationship. While the contribution of tax amnesty revenue on tax revenue in accordance with the determination test is 0.626 or 62.6%. Result of t test also show tcount 3,422 and ttabel 2,364 which mean X variable influence to Y variable significantly. The result of the regression is Y = 238.347 + 0.980 X, the constant a = 238.347 can be interpreted if tax amnesty revenue (X) is zero (0), then the tax revenue (Y) is 238.347. The value of coefficient b = 0.980 can be interpreted if every increase of tax amnesty acceptance (X) is one (1), then the level of tax revenue (Y) will increase 0,980.